INSPIRING LECTURE MANAJEMEN STRATEGIK DI PRODI ADMINISTRASI PUBLIK FISIP UNIVERSITAS SULTAN AGENG TIRTAYASA: SEBUAH PENGALAMAN UNIK BAGI DOSEN DAN MAHASISWA - Ayuning Budiati (SEBA: Jurnal Pengabdian kepada Masyarakat, 2025)
A very valuable experience when selected as one of the lecturers in the Inspiring Lecturer Program. Very grateful and happy, even though the author has become a lecturer and facilitator at a Foundation outside the campus about character building for classes throughout Indonesia and about national insight. There is something different about this program because it contains lecturers from all over Indonesia and all are full of enthusiasm and innovation in building education in Indonesia and are very enthusiastic about producing the next generation of the nation who are innovative, creative and transformative with appropriate and up-to-date techniques. The Inspiring Lecture Program has succeeded in leveraging the output and outcome of the learning process of the Strategic Management of Public Organizations Course for 3rd semester students of the FISIP, Sultan Ageng Tirtayasa University. The students become the center of learning, learn effectively, have GRIT, increase their eagle view and helicopter view.Keywords: strategic management, inspiring lecture, lecturer student